The awakening and silence in literature and psychoanalysis - Beserra Fontenele, Laéria (Revista de Psicologia, 2022)
Assuming that the singularity of the psychoanalytic experience, despite the difficulties it offers to its transmission, cannot be taken as ineffable in the mystical way and that summons the production of an unknown knowledge, the lecturer addresses the different modalities of experience for how the silence present in a course of analysis and the way they precipitate at its end. Therefore, she goes through the theme of silence in its relationship with the unconscious and the drive from the consideration of the phallic logic’s limits in order to understand what, in the symptom, appeals to the side of meaning and to the experience of awakening. It also uses literary testimonies to think about the relationship between awakening and silence in its relationship with the end of analysis. The conference was given on the occasion of the I International Colloquium of Psychoanalysis of the Freudian Body School of Psychoanalysis: The awakening, which took place at the Italian Institute in the city of Rio de Janeiro from April 12 to 14, 2007.